2022
DOI: 10.1530/eje-21-1046
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINOLOGY IN PREGNANCY: Targeting metabolic health promotion to optimise maternal and offspring health

Abstract: There is an increase in maternal metabolic burden due to the rise in pregnancies complicated by obesity, gestational diabetes, type 2 diabetes and polycystic ovary syndrome. Metabolic dysfunction during pregnancy is associated with increased risks of long-term morbidity and mortality for women and their offspring. Lifestyle interventions in pregnancy in women at risk of metabolic dysfunction, have demonstrated short term improvements such as reduced gestational weight gain and lowered risk of gestational diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Substantial evidence demonstrates that maternal metabolic factors, before and during pregnancy, adversely affect offspring growth or adiposity in utero and after birth, leading to increased risk for metabolic dysfunction and cardiovascular disease into adulthood 71,72 . A recent systematic review and evidence synthesis examined the associations between maternal metabolic exposures and offspring weight and/or adiposity using data from 76 published human ( n = 38) and animal ( n = 38) studies 73 .…”
Section: The Prenatal Exposome: Fetal Exposures and Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence demonstrates that maternal metabolic factors, before and during pregnancy, adversely affect offspring growth or adiposity in utero and after birth, leading to increased risk for metabolic dysfunction and cardiovascular disease into adulthood 71,72 . A recent systematic review and evidence synthesis examined the associations between maternal metabolic exposures and offspring weight and/or adiposity using data from 76 published human ( n = 38) and animal ( n = 38) studies 73 .…”
Section: The Prenatal Exposome: Fetal Exposures and Programmingmentioning
confidence: 99%
“…Substantial evidence demonstrates that maternal metabolic factors, before and during pregnancy, adversely affect offspring growth or adiposity in utero and after birth, leading to increased risk for metabolic dysfunction and cardiovascular disease into adulthood. 71,72 A recent systematic review and evidence synthesis examined the associations between maternal metabolic exposures and offspring weight and/or adiposity using data from 76 published human (n = 38) and animal (n = 38) studies. 73 Maternal obesity, diabetes, and poor dietary quality (high fat, high sugar, or high calorie diets) were found to be associated with greater risk of high birth weight or higher BMI during childhood in humans, as well as greater risk of excess adipose tissue accumulation in both human and animal offspring.…”
Section: Maternal Metabolic Factorsmentioning
confidence: 99%
“…28,29 One explanation for an increase in GDM diagnosis during COVID-19 may relate to lockdown behaviours, such as increased consumption of snacks and carbohydrates 30,31 and reduced exercise, 32 leading to weight gain, 33 an independent risk factor for GDM. 34…”
Section: Clinical Interpretationmentioning
confidence: 99%
“…Both conditions are associated with in utero complications, including stillbirth, fetal macrosomia, being large for gestational age (LGA), preterm birth, and post-delivery complications such as perinatal death, neonatal death, or infant mortality. These conditions are correlated with an increased risk of postpartum depression, stroke, the development of cardiometabolic diseases, or T2DM in the future [ 26 , 33 ]. According to Egan et al, the risk of developing T2DM within 15 years of delivery was found to be 30% for women with GDM at an optimal weight, compared to 70% for obese women with GDM [ 28 ].…”
Section: Obstetric Complications In Women With Obesity and Diabetes M...mentioning
confidence: 99%